Nature of Lightning Hazard and Distribution during Post Monsoon Season in Makwanpur District (The Geographic Base, 2024)
Nepal is one of the global hotspots for lightning events, with lightning strikes constituting a major natural disaster in the country. Among Nepal's districts, Makwanpur is particularly vulnerable to destructive thunderbolts. According to the DRR Portal, thunderbolts have caused 83 fatalities and 296 injuries in the district since 2011. This study focuses on analyzing the nature, distribution, and occurrence of Lightning in Makwanpur District during the late monsoon period, specifically from September to October 2024. The study observes lightning activity during this pre-winter season. A 32-day observation was conducted using satellite-enabled tools to monitor lightning occurrences, their proximity, and their characteristics, including power and polarity. For this purpose, Meteologix, an online Lightning and weather Monitoring tool was used. The finding shows that south-eastern part of Makwanpur district shows high concentration of lightning.